Resisting the rat race: Self-sufficiency as a search for resonance in rural Sweden (Sociologisk Forskning, 2020)
When people feel they have to run faster and faster just to keep up, it is a personal experience of the acceleration that characterises late modern society. In reaction, some people attempt to escape “the rat race” by aiming to live self-sufficiently in the countryside. This article presents a text analysis of 35 letters from the magazine Åter, where people share their experiences of moving. The analysis focuses on the authors’ motivations for the move, their criticism of mainstream society and their experiences of time, temporality and competing time norms in their new life. Rosa’s concepts of acceleration, alienation and resonance, and Adam’s concept of abstract and standardised clock time, provide the theoretical framework for the analysis. The study concludes that the authors of letters search for resonance and to a large degree they have also found it, especially since the authors experience their work as meaningful and live according to their ideological values. Self-sufficiency is an individual form of coping, but simultaneously choosing to live differently is a practice of constructive resistance to mainstream consumption and work norms.
Keywords: time; temporality; constructive resistance; voluntary simplicity; self-sufficiency; resonance; acceleration